The operators the wild and terrifying inside story of America's war in Afghanistan - Hastings, Michael 1980-2013 (Plume Books, 2012)
Reveals the high-stakes maneuvers and bureaucratic infighting of the military commanders involved in the Afghan War, describing patrol missions into the Afghan hinterlands and late-night sessions of military advisors.